THE NEW DIAGNOSTIC FEATURES OF CD138 (SYNDECAN-1) IN MULTIPLE MYELOMA - A. F. Karamysheva (Успехи молекулярной онкологии, 2015)
Syndecan-1 (CD138) is one of the main cell markers used in flow cytometric analysis of multiple myeloma (MM) cells. CD138 and several other markers – CD19, CD45, CD56 – which are often used in order to characterize MM and give the possibility to differentiate MM cells from the normal plasmocytes are described. Only CD138-expressing MM plasma cells are usually taken into account in MM analysis. The current literature data point out that CD138-negative MM plasma cells could be important for MM prognosis, as well. This cell population demonstrates certain properties that are typical to the cancer stem cells. CD138-negative cell population is characterized by higher proliferation, clonogenicity, engraftment in immunodeficient mice as compared to CD138 expressing plasma cells. Besides that, CD138-negative cells were more resistant than CD138-positive cells to the drugs that are used in MM chemotherapy. CD138-negative plasma cells are able to produce CD138 expressing cells upon a long-term culture in vitro and thus to reproduce the heterogenic in CD138 expression population of MM plasma cells. The results of these investigations, as well as statistical data indicating the worse overall survival of CD138 low expressing MM patients point out that CD138-negative population of MM plasma cells should be taken into consideration in MM analysis. Thus, it could be important to find the new markers distinguishing the plasma cell population differing in CD138 expression. Vascular endothelial growth factor receptor VEGFR3 was found to be a new marker with such properties.